Pengadaan Dan Pendampingan Pelestarian Lingkungan Dalam Mendampingi Kelompok Tani Pelestarian Hutan - Ani Pratiwi; Sri Baniyanti; Sufiarni Sufiarni; Safrin Salam (Journal of Innovative and Creativity, 2025)
Environmental conservation in Mangga Dua Village, in maintaining ecosystem balance and supporting sustainable livelihoods, is crucial and is progressing well thanks to the active participation of the community, particularly farmer groups, demonstrating the integration of wildlife conservation and ecosystem-based economic development. Forest farmer groups play a role in forestry development through various productive activities, such as nurseries, non-timber forest product cultivation, and utilization of environmental services. This research seeks to identify, analyze, and evaluate the effectiveness of the mentoring program implemented for Forest Farmer Groups to support environmental preservation and to sustain forest ecosystems and biodiversity. The mentorship process and environmental conservation within Forest Farmer Groups (KTH) are examined in this study using a case study methodology and a qualitative approach. Mangga Dua Village, Kendari District, Kendari Regency, the intended location for the environmental conservation mentorship program, served as the study's site. The findings show an enhancement in the knowledge and abilities of KTH members, suggesting that the mentoring program has effectively boosted the knowledge and skills of KTH members prior to mentoring, as most KTH members possess only a fundamental grasp of forest management. Following mentorship, they can: 1) Recognize economically valuable local and non-timber plant species, 2) Implement suitable nursery and planting methods for reforestation, 3) Grasp the significance of forests' ecological roles, including the regulation of water systems and habitats for wildlife. Therefore, it can be determined that the empowerment and capacity building of this program has succeeded in changing KTH from mere objects to the main subjects in conservation efforts, economic and ecological integration, the success of mentoring is greatly influenced by its ability to integrate environmental conservation with improving economic welfare, social and institutional strengthening, mentoring has succeeded in building strong social capital among members of KTH. This shows that forest conservation can be achieved through a bottom-up approach that empowers local communities, making them the vanguard in maintaining environmental sustainability.